Ocena prometne varnosti pri voznikih invalidih amaterjih - Črnivec, Rajko (Medicinski razgledi, 2001)
The pilot study comprised a random sample of 30 male amateur drivers (first group, category B according to the Slovene traffic safety legislation) and a random sample of 30 male disabled amateur drivers (first group, category B) who had their last medical examination in 1998. A comparison of the two samples showed that male nondisabled drivers, especially those with severe impairments and a limited driving ability, more frequently caused traffic offences and accidents. Disabled drivers were older and more frequently had severe health impairments than nondisabled drivers. Most disabled drivers had had their cars adapted to the type of their disability. Periodic health check-ups and driving tests were also required. As was assumed in our hypothesis, disabled drivers clearly present a lesser threat to traffic safetyin Slovenia, so they should have some benefits, especially for motor third party insurance, but also other benefits. However, defining the extent, content and rate of these benefits will require a more thorough research aver a longer observation period. The current Slovene traffic safety legislation does not prescribe any benefits for disabled amateur drivers.
Keywords: Automobile driving; Avtomobilska vožnja; Disabled; Nesreče prometne; Vozniki avtomobila, preiskava; Accidents, traffic; Automobile driver examination; Delovna sposobnost, ocena; Health status; Zdravstveno stanje; vozniki; Disability evaluation; vožnja; prometna varnost; invalidi